Can the Myocardial Performance Index Be Used as a New Predictive Factor for a Poor Prognosis in Fetuses With Idiopathic Polyhydramnios?. (7th November 2016) - Gezer, Cenk; Ekin, Atalay; Ozeren, Mehmet; Taner, Cuneyt Eftal; Mat, Emre; Solmaz, Ulas
Abstract : Objectives: The purpose of this study was to determine whether there are any changes in cardiac function in fetuses with idiopathic polyhydramnios and also to evaluate the value of the myocardial performance index for prediction of adverse perinatal outcomes. Methods: A prospective case‐control study was conducted with a total of 134 fetuses between 24 and 40 weeks' gestation. Polyhydramnios was defined as an amniotic fluid index of greater than 24 cm. Seventy‐three fetuses of healthy mothers were assigned as the control group whereas 36 fetuses with an amniotic fluid index of 24 to 34 cm constituted the nonsevere polyhydramnios group, and 31 fetuses with an amniotic fluid index of 35 cm or greater constituted the severe polyhydramnios group. Fetal echocardiography was performed to compare cardiac function parameters among groups. To determine which perinatal outcomes were independently associated with an increased myocardial performance index, a multivariate logistic regression analysis was performed. Results: The myocardial performance index was significantly higher in polyhydramnios groups compared with controls ( P < .001). Among fetuses with polyhydramnios, the myocardial performance index was significantly higher in severe polyhydramnios compared with nonsevere polyhydramnios ( P = .003). An increased myocardial performance index in polyhydramnios was independently associated with nonreassuring fetal status (odds ratio, 2.12; 95% confidence interval, 1.41–4.53; P = .005), emergency cesarean delivery (odds ratio, 1.54; 95% confidence interval, 1.12–2.37; P = .025), and respiratory distress syndrome (odds ratio, 1.79; 95% confidence interval, 1.21–3.87; P = .012). Conclusions: An increased myocardial performance index is an early indicator of adverse perinatal outcomes in pregnancies complicated by idiopathic polyhydramnios.